ANTIHYPERLIPIDEMIC EFFECT OF ASPARAGUS GONOCLADOS BAKER AGAINST CHOLESTEROL DIET INDUCED HYPERLIPIDEMIA IN RATS. - NALLAM JAHNAVI; PRASAD. P. NAIDU; KOTESWARA RAO. A; KARUNASREE. C. P (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: To evaluate the antihyperlipidemic potential of the Ethanolic Extract of Root tubers of Asparagus gonoclados (EERAG) in cholesterol diet induced hyperlipidemic rats. Methods: Wistar albino rats were randomly divided into five groups of six each. Group-I served as normal control. Groups II to V were given 5% cholesterol diet for 3 months to induce hyperlipidemia, and for last 28 days were administered either: 0.5ml water/saline for Group- I; cholesterol diet (5%) for Group-II; Standard drug Rosuvastatin (20mg/kg body weight) for Group-III; A.gonoclados extract at 250 mg/kg bodyweight for Group-IV and 500mg/kg body weight for Group-V. The effects of EERAG on serum lipid profile, Body Weight and antioxidant enzymes (Superoxide Dismutase and Catalase) were assessed and compared. Results: Cholesterol diet induced hyperlipidemic rats showed an significant (P<0.001) increase in the plasma concentration of Total Cholesterol (TC), Triglycerides (TG), Low-Density Lipoprotein cholesterol (LDL-c), Very Low-Density Lipoprotein cholesterol (VLDL-c) and body weight. Decrease in High Density Lipoproteins Cholesterol (HDL-c) and antioxidant enzymes were observed when compared to normal control rats. Co-administration of EERAG and standard drug Rosuvastatin with high cholesterol diet caused a significant decrease (p<0.001) in the concentration of serum TC, VLDL, TG, body weight and increase in the HDL-c and antioxidant enzymes when compared with cholesterol fed control rats. Conclusion: The result suggests lipid lowering and antioxidant potential of effect of A. gonoclados, which serves as a new potential herbal product for preventing hyperlipidemia.